Pengaruh Varian Produk, Harga dan Promosi Terhadap Keputusan Pembelian pada Brownies Cinta Karanganyar - Anita Susilowati; Sumaryanto (Teewan Journal Solutions, 2026)
This study was designed to empirically test the significance of the influence of product variants (X₁), price (X₂), and promotion (X₃) on purchasing decisions (Y) for Brownies Cinta Karanganyar. The methodology used was a quantitative survey of 100 respondents selected using purposive sampling techniques. The data were analysed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results of the study concluded as follows: (1) The regression equation formed is Y = 1.281 + 0.254X₁ + 0.387X₂ + 0.158X₃ + e. (2) Partially, the t-test confirmed that product variety, price, and promotion had a significant effect on purchasing decisions. (3) Simultaneously, the F test shows that the regression model is significant. (4) The coefficient of determination (Adjusted R Square) is 0.511, which means that the simultaneous contribution of the three independent variables to the dependent variable is 51.1%, while the remaining 48.9% is influenced by other variables such as product quality, taste, and location.